Double immune reconstitution therapy: Cladribine after alemtuzumab in the treatment of multiple sclerosis. (31st October 2021) - Adamec, Ivan; Jovanović, Ivan; Krbot Skorić, Magdalena; Habek, Mario
Abstract: Background and purpose: Alemtuzumab, a monoclonal anti‐CD52 antibody, and cladribine, a purine nucleoside analogue, are used for the treatment of highly active relapsing‐remitting multiple sclerosis (MS). Both are administered as two short yearly courses but possess the ability to induce long‐term remission, labeling them as immune reconstitution therapies. Although disease activity after alemtuzumab administration is rare, there are a small number of people with MS who will experience disease activity despite repeated alemtuzumab treatment. Methods: We report on six patients with MS who experienced disease activity after alemtuzumab and were subsequently treated with cladribine and followed up for up to 2 years. Results: None of the patients experienced relapses during the follow‐up period and in all patients Expanded Disability Status Scale values remained unchanged. All patients had lymphopenia at one time point. In patients 1 and 2, at the nadir, the lymphopenia was grade 1, in patient 3 it was grade 2 and in patients 5 and 6 it was grade 3. No infections or malignancies were recorded during the follow‐up. Conclusion: This report provides a framework for treating people with MS with sequential immune reconstitution therapies. Abstract : Although disease activity after alemtuzumab administration is rare, there are a small number of people with multiple sclerosis (MS) who will experience disease activity despite repeated alemtuzumab treatment. We report on six patients with MS who experienced disease activity after alemtuzumab and were subsequently treated with cladribine, with favorable clinical and magnetic resonance imaging‐based effectiveness and a good safety profile after 2‐year follow‐up.